Legal Study on Applications to Leave Islam in Negeri Sembilan Malaysia: Case Study Noraini A/P Imara Musa - SAPUTRA, Deris Arista (Journal of Political And Legal Sovereignty, 2025)
Purpose:The urgency of this research lies in the importance of understanding how the Sharia Court applies locus standi provisions in handling these requests, which directly have implications for access to justice. This research aims to analyze juridically the decision of the Negeri Sembilan Syariah Court in the case of Noraini A/P Imara Musa, which was rejected based on the provisions of the Enakmen for Islamic Religious Administration (Negeri Sembilan) 2003 and the 2009 amendment.Methodology:The method used is qualitative research with a juridical-normative and juridical-empirical approach, through document studies, content analysis, and legal interpretation.Findings:The research findings indicate that the Court acted within its authority and applicable legal provisions, rejecting the petition because the applicant failed to meet the locus standi requirements stipulated in domestic law. This finding underscores the importance of procedural consistency in maintaining the integrity of Sharia law and preventing the Court's jurisdiction from being undermined.Implication:This research contributes to a richer understanding of the boundaries of law and religious protection within the context of an Islamic state. The implications of this research provide opportunities for strengthening the Sharia legal system and harmonizing it across countries. Future research is recommended to explore similar issues comparatively across countries to broaden the perspective of contemporary Islamic law.